Understanding Diabetes Care Barriers Through Community Voices: A Brief Qualitative Report from Jefferson County, Kentucky - Hasan, Md Rakibul (Asian Journal of Public Health and Nursing, 2025)
Background: Type 2 diabetes is a significant public health concern in Jefferson County, Kentucky, exacerbated by socioeconomic barriers influencing care access and disease management. This qualitative study explored community-perceived barriers impacting diabetes self-management among local adults. Methods: Guided by the Theory of Planned Behavior, this qualitative study involved thematic analysis (Braun and Clarke’s method) of open-ended responses collected through an online questionnaire from six purposively selected adults (≥18 years) with physician-diagnosed type 2 diabetes in Jefferson County. Results: Participants described several structural barriers affecting their diabetes care, primarily highlighting medication affordability (83%), transportation difficulties (67%), and inadequate access to healthy food (67%). Additional qualitative themes revealed concerns related to insufficient flexibility of healthcare services and personal time constraints. Participants further suggested community-informed strategies, including subsidized medication programs, enhanced transportation services, increased availability of virtual healthcare, and improved local access to affordable fitness facilities and nutritious foods. Conclusion: Qualitative insights underscore a substantial gap between diabetes care intentions and achievable self-management practices due to persistent systemic barriers. Addressing these barriers through targeted, community-driven solutions could meaningfully improve diabetes outcomes in Jefferson County